Use of Sodium Metabisulphide as An Alternative Depresant in Selective Flotation of Lead and Copper - Tanriverdi, Mehmet; Ozturk, Emre (Asian Journal of Chemistry, 2012)
In this study, complex lead-zinc-copper ore located in the territory of Canakkale Province, Yenice County, Kalkim District has been worked on. Physical and mineralogical characteristics of the ore showed that the appropriate ore enrichment method is flotation. The first aim was to determine the optimum flotation conditions for the further studies. The flotation tests to determine the type of depressant were completed to use in selective flotation circuit of lead and copper. Potassium dichromate is widely used as a depressant of this type of ores. However, potassium dichromate is an undesirable chemical with carcinogen impacts and environmental drawbacks. Many alternatives of potassium dichromate is studied in recent years such as sodium metabisulphide. Sodium metabisulphide is less dangerous than potassium dichromate for environment and human health. In this study, the ore was beneficiated using sodium metabisulphide and 89.74 % cumulative recovery with 66.32 % Pb content in the final lead concentrate and 35.67 % cumulative recovery with 24.94 % Cu content in the final copper concentrate was obtained. The positive and negative aspects of sodium metabisulphide with respect to potassium dichromate are discussed regarding the experimental studies.